PENGARUH TINGKAT PENDIDIKAN, KESADARAN PAJAK, DAN PENERAPAN SISTEM CORETAX TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI: STUDI EMPIRIS PADA KPP PRATAMA TARAKAN - Diva Nadya Putri; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This study aims to examine the influence of educational level, tax awareness, and the implementation of the Coretax system on individual taxpayer compliance. The respondents of this study are individual taxpayers registered at KPP Pratama Tarakan. The sampling technique used in this study is purposive sampling, and the data source is primary data collected through questionnaires. The questionnaire employed a Likert scale ranging from 1 to 5. The total sample consisted of 102 respondents. Data analysis was conducted using multiple linear regression with IBM SPSS 26. The results of the study indicate that educational level, tax awareness, and the implementation of the Coretax system have an influence on individual taxpayer compliance.